The immersive experience of virtual reality during chemotherapy in patients with early breast and ovarian cancers: The patient’s dream study - Fabi, Alessandra; Fotia, Luana; Giuseppini, Federico; Gaeta, Arianna; Falcicchio, Chiara; Giuliani, Gabriele; Savarese, Antonella; Taraborelli, Emanuela; Rossi, Valentina; Malaguti, Paola; Giannarelli, Diana; Pugliese, Patrizia; et al. (Frontiers in Oncology, 2022)
Background: A virtual reality experience (VRE) could represent a viable non-pharmacological intervention to reduce and better manage the main factors of psychophysical distress related to the diagnosis and treatment of cancer. Aim: The "Patient's Dream" study was a two-arm randomized controlled trial conducted at the Regina Elena National Cancer Institute – IRCCS (Rome, Italy) from April 2019 to January 2020 to evaluate VRE impact in patients affected by breast or ovarian cancer. Before starting the first cycle of chemotherapy (CT), patients were randomized to receive the VRE (VRE arm) as "distraction therapy" or to entertain themselves with conventional means (control arm). The primary aims were the assessment of psychological distress, anxiety and quality of life between the two study arms. Secondary endpoints were the perceived time during the first course of CT and the acute and late toxicity. Results: Collected data underline the absence of prevalent disturbs of anxiety and depression in both groups. Nevertheless, even if the state anxiety values before and after CT decreased in both groups, this reduction was statistically significant over time only in the VRE arm. The duration of therapy perceived by patients undergoing distraction therapy was significantly shorter when compared to the control group. The use of VRE during the first CT cycle appeared to reduce asthenia outcomes. Conclusion: Obtained data suggest that the VRE positively influenced the levels of state anxiety among cancer patients and support the continuous research on VRE as a distraction intervention, with the aim to meet the clinical need for effective nonpharmacologic adjunctive therapies. Trial registration: NCT05234996